Recent Advances in Decision Making - Rakus-Andersson, Elisabeth; Yager, Ronald R.; Ichalkaranje, Nikhil (Studies in Computational Intelligence,, 2009)
Intelligent paradigms are increasingly finding their ways in the design and development of decision support systems. This book presents a sample of recent research results from key researchers. The contributions include: Introduction to intelligent systems in decision making A new method of ranking intuitionistic fuzzy alternatives Fuzzy rule base model identification by bacterial memetic algorithms Discovering associations with uncertainty from large databases Dempster-Shafer structures, monotonic set measures and decision making Interpretable decision-making models A General methodology for managerial decision making Supporting decision making via verbalization of data analysis results using linguistic data summaries Computational intelligence in medical decisions making This book is directed to the researchers, graduate students, professors, decision makers and to those who are interested to investigate intelligent paradigms in decision making.